2022
DOI: 10.3390/ijms232314857
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Actual Applications of the Polymers Containing Acidic P–OH Fragments: Part 1. Polyphosphodiesters

Abstract: Among natural and synthetic polymers, main-chain phosphorus-containing polyacids (PCPAs) (polyphosphodiesters), stand in a unique position at the intersection of chemistry, physics, biology and medicine. The structural similarity of polyphosphodiesters PCPAs to natural nucleic and teichoic acids, their biocompatibility, mimicking to biomolecules providing the ‘stealth effect’, high bone mineral affinity of polyphosphodiesters resulting in biomineralization at physiological conditions, and adjustable hydrolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 134 publications
1
3
0
Order By: Relevance
“…Following up on the focus of previous studies and the results of subcutaneous implantation experiments in the present work, we considered it more promising to investigate the potential of pCAp as a BMS without and with the addition of PEPA. As mentioned in the introduction, PEPA has a high affinity toward CPCs, , and its osteoinductivity was confirmed previously by in vitro experiments. , As applied to crystalline pCAp, the high binding strength of PEPA has been proven in our recent study …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Following up on the focus of previous studies and the results of subcutaneous implantation experiments in the present work, we considered it more promising to investigate the potential of pCAp as a BMS without and with the addition of PEPA. As mentioned in the introduction, PEPA has a high affinity toward CPCs, , and its osteoinductivity was confirmed previously by in vitro experiments. , As applied to crystalline pCAp, the high binding strength of PEPA has been proven in our recent study …”
Section: Resultssupporting
confidence: 74%
“…Among phosphorus-containing polyacids, poly­(ethylene phosphoric acid) (−OP­(O)­OCH 2 CH 2 −) n (PEPA) is attractive because of its biodegradability . In vitro studies of PEPA confirmed its low cytotoxicity, high bone mineral affinity, , and ability to selectively inhibit human osteoclast functions . In vitro osteoinductivity of the Ca 2+ and Na + salts of PEPA was recently discovered by our group and by Iwasaki and co-workers, respectively, but in vivo osteoinductivity of PEPA in combination with CPCs remains unexplored.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar compatibilizers have been widely used in dentistry [ 68 , 69 ]; however, until recently, amphiphilic derivatives of phosphoric acid have not been studied as compatibilizers for BMS/polyester composites. Among phosphorus-containing polyacids, poly(phosphodiester)s seem to be promising in view of their BM affinity [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and osteoinductivity [ 69 , 75 , 76 , 77 ]. In a recent study [ 78 ], we demonstrated a positive impact of an amphiphilic copolymer containing PCL and poly(ethylene phosphoric acid) (PEPA) blocks on the morphology of PCL/HAp fibrous scaffolds, prepared with the electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%